'That's what I call a man': representations of racialised and classed masculinities in the UK print media. (20th March 2015) - Baker, Paul; Levon, Erez
Abstract : According to Connell (1995), "being a man" involves actively positioning one's self in relation to culturally dominant images of masculinity. Yet, crucially, these images change depending on the social and historical context. In this paper, we examine contemporary discourses of masculinity as they are represented in the British press. In particular, we focus on the ways in which masculine representations are both racialized and classed, and how they are positioned in relation to one another within a broader ideological field of gender and power. Analyses are based on a quantitative and qualitative analysis of a large corpus (35.5 million words) of newspaper articles on masculinity that appeared in the UK between 2003 and 2011. Our findings underscore the importance of adopting an intersectional approach to the study of language and masculinity, and provide support for recent critical re-evaluations of the foundational concept of hegemonic masculinity.